The contribution of a master's degree to clinical practice. - Skogsaas, Bente (Norwegian Journal of Clinical Nursing / Sykepleien Forskning, 2017)
Background: Educational programmes in advanced practice nursing are switching from specialist training to a master's level education. In general, there is a positive attitude towards master's degrees, but some have objections regarding ''academisation'' and 'over-qualification'. Objective: To investigate the expectations that the anaesthesiology and intensive care professions have of master's level competence. Method: We conducted three focus group interviews with anaesthesiology and intensive care nurses in three health trusts. They were managers, advanced practice nurse mentors, experienced nurses and recent nursing graduates. We used thematic content analysis to analyse and interpret meaning systems. The expectations of informants regarding master's level competence were gleaned from the positive and negative statements made during the interviews. Results: At the master's degree level, informants expect that nurses' scientific language and critical thinking ability will be further developed, be integrated into professional knowledge and professional practice, and be reflected in the way nurses present themselves and interact. Many expect nurses with master's degrees to have a higher level of competence and greater potential for satisfying the requirement of evidence-based practice (EBP). Anaesthesiology and intensive care nursing are regarded as practice-oriented professions, and there are concerns as to whether master's degree programmes provide an equally high skill level and theoretical knowledge as specialist training. Conclusion: The added value of a master's degree programme is found in the scientific language and critical thinking skills, as well as in the application of evidence-based practice. Health trusts and educational institutions should cooperate closely on developing educational models, study programmes and pedagogical approaches so that the skill level is maintained in a master's degree programme.